ID: 248. Issue 1 (November 2015) - Parker, Dane; Planet, Paul; Cohen, Taylor; Smith, Hannah; Leon, Justinne; Ryan, Chanelle; Hammer, Tobin; Fierer, Noah; Cheng, Emily; Prince, Alice
<x xml:space="preserve">Abstract</x> Much of the morbidity and mortality associated with influenza respiratory infection is due to bacterial co-infection with pathogens that colonize the upper respiratory tract such as MRSA and Streptococcus pneumoniae. Several immune mechanisms have been identified that account for the interaction between viruses and bacteria, less well understood is how influenza increases susceptibility to bacterial pneumonia. Here we show that the immune response to infection with influenza causes an increase and restructuring of the upper respiratory microbiota in WT but not Il28r−/− mice, lacking the receptor for the type III interferons. Mice lacking IL-28R fail to induce STAT-1 phosphorylation and its regulation by SOCS1. The Il28r−/− mice have increased expression of IL-22 as well as Ngal and RegIIIg in the nasal cavity, the source of organisms that would be aspirated to cause pneumonia. Proteomic analysis reveals changes in several cytoskeletal proteins that contribute to barrier function in the nasal epithelium that may contribute to the effects of IL-28 signaling on the microbiota. The importance of the effects of IL-28 signaling in the pathogenesis of MRSA pneumonia post influenza were confirmed by showing that WT mice nasally colonized before or after influenza infection had significantly higher levels of infection in the upper airways, as well as significantly greater susceptibility to MRSA pneumonia compared to Il28r−/− mice. Our results suggest that the activation of the type III interferons in response to influenza has a major effect in expanding the upper airway microbiome and increasing susceptibility to lower respiratory tract infection.